Futurecasting ecological research: the rise of technoecology. Issue 5 (8th May 2018) - Allan, Blake M.; Nimmo, Dale G.; Ierodiaconou, Daniel; VanDerWal, Jeremy; Koh, Lian Pin; Ritchie, Euan G.
Abstract: Increasingly complex research questions and global challenges (e.g., climate change and biodiversity loss) are driving rapid development, refinement, and uses of technology in ecology. This trend is spawning a distinct sub‐discipline, here termed "technoecology." We highlight recent ground‐breaking and transformative technological advances for studying species and environments: bio‐batteries, low‐power and long‐range telemetry, the Internet of things, swarm theory, 3D printing, mapping molecular movement, and low‐power computers. These technologies have the potential to revolutionize ecology by providing "next‐generation" ecological data, particularly when integrated with each other, and in doing so could be applied to address a diverse range of requirements (e.g., pest and wildlife management, informing environmental policy and decision making). Critical to technoecology's rate of advancement and uptake by ecologists and environmental managers will be fostering increased interdisciplinary collaboration. Ideally, such partnerships will span the conception, implementation, and enhancement phases of ideas, bridging the university, public, and private sectors.